Developments in the Division of Civil Liability in the French Civil Code in the light of Decree No. 131 of 2016 - a comparaative study – - Zina Monhim Madhar; Hewa Ibrahim Qadir (Zanco Journal of Humanity Sciences)
This research the research presents a comparative analytical study that seeks to clarify updates in the division of civil responsibility in the French Civil Code since its issuance in 1804 through the amendments made to it, especially those included in Decree No. (131) of 2016 amending the mentioned law, down to the civil responsibility reform project (Civil Liability Reform Project March 2017), And a statement of the position of the Iraqi civil law on all of this. The study concluded that the common division of civil liability into contractual and tort sources stems from jurisprudence and does not exist in French civil law, And that the term liability did not exist in the French civil code at the time of its issuance in 1804, It was first introduced under the Defective Products Liability Act of 1998, And that Decree No. (131) of 2016 has made the articles related to tort liability under the title of non-contractual liability Which, in turn, is considered the starting point for reforming the theory of civil liability, for which jurisprudence has prepared several projects, and from which the civil liability reform project has been derived (Civil Liability Reform Project March 2017) Who adopted several divisions of civil liability, including contractual and non-contractual liability, and special systems for liability, We also recommended the Iraqi legislator to adopt the same steps followed by the French legislator by introducing general provisions for contractual and non-contractual liability in the Iraqi civil law by making the necessary amendments with the aim of developing the civil law.